EFFECTS OF RESVERATROL ON HUMAN HEALTH - Duyuran, Rumeysa; Çiçek, Hülya; Bincan, Baran (Göbeklitepe Medical Science Journal, 2022)
Grape is a perennial plant and its fruit and leaves are consumed as food. Its homeland is thought to be the Middle East. There is evidence that the cultivation of this plant began 7-8 thousand years ago. When we look at the content of ripe grapes, 100 grams of grapes contain 69 kilos of energy, 81% of them are water, 18% are carbohydrates, 1% is protein, and contain very little fat, vitamin K and vitamin E. Resveratrol (RSV) was first produced in the early 1930s by the medicinal plant Veratrum grandifolium Loes. fil., many studies have shown that it will be useful in clinical use due to the flavonoids and polyphenolic compounds found in grapes. RSV is a natural non-flavonoid polyphenol belonging to the stilbenoid group, especially found in the skin of black grapes. Besides grapes, it is also found in various plants such as strawberries, blueberries, pomegranates, mulberries, pistachios and peanuts. It is thought that RSV, which is found in dietary components, may have many effects such as antioxidant, anti-inflammatory, anticarcinogenic, neuroprotective, cardioprotective, lipid regulating, antidiabetic and life-prolonging. The potential benefits of RSV have been widely studied in some animal experiments, with positive results. Clinical trials in humans, on the other hand, are less numerous and the results are not yet conclusive. Considering the scientific studies done so far, it has been determined that RSV has tumor-suppressive properties in many stages of cancer. It is a powerful antioxidant that can prevent cell damage caused by free radicals. Radiotherapy or chemotherapy causes inflammation in neighboring cells of cancer cells, while RSV stimulates leukocytes to eliminate these lysed cells, thereby accelerating their apoptosis. RSV improves lipid profile by reducing hepatic 3-hydroxy-3-methyl-glutaryl-CoA reductase in mRNA expression and potentially leading to reverse cholesterol transport. It has been shown that it can lower blood pressure by increasing endothelial nitric oxide (NO) production, reducing oxidative damage and calcium influx. While RSV does not cause any changes in blood pressure acutely, when used for a long time, it improves endothelial function, especially in hypertensive women with higher LDL cholesterol levels. Because polyphenols reduce atherogenesis by preventing low-density lipoprotein oxidation, fat accumulation and platelet aggregation. Down-regulation of inflammatory pathways and regular signaling, decrease in IL-6, TNF alpha, interferon-gamma, Herp, IL-8 and leptin levels, down-regulation of leukocyte adhesion molecules, changes in mRNAs involved in inflammatory modulation, anti-inflammatory effect through an increase in IL-10 plasma levels shows. Recent studies have shown that RSV has a curative effect on Alzheimer's disease and prevents neurological damage in case of cerebral ischemia. It has a protective effect against chronic obstructive pulmonary disease. Some recent studies on RSV have determined that it prolongs lifespan in some yeasts, threadworms, fruit flies, fish, and obese mice. Keywords: Grape seeds, antioxidant, effects of resveratrol.